Institutional aspects in regulating interaction between financial and innovation sectors - Rakhmetova, А.М.; Kalkabayeva, G.M. (BUKETOV BUSINESS REVIEW, 2020)
Object: The scientific paper focuses on issues of inefficient intersectoral interaction through the prism of an institutional methodological approach. In particular, the authors aim to investigate and identify problems that limit the harmonious and mutually beneficial interaction of subjects of the financial and credit and innovation sectors in the modern conditions of the Kazakhstani economy. Methods: Based on the use of comparative, statistical and expert analysis, the authors conclude that it is necessary to level the existing problem nodes by improving the existing institutional environment in terms of developing financial, real and regulatory innovations, further developing the institutional infrastructure, and an optimal combination of formal and informal institutions. Findings: It is recommended to change the current paradigm of regulatory institutions implementation in the direction of preventive and stimulating regulation of subjects in both sectors at the same time in order to reduce the existing asymmetry. Conclusions: The article considers the sources of financial and credit support for the innovation sector, identifies problems in financing investment and innovation projects in Kazakhstan based on a comprehensive analysis of the costs of research and development, bank lending, foreign investment, investment potential of the pension and insurance sectors, and development institutions.